Nation-building five Southeast Asian histories - Wang, Gungwu; Institute of Southeast Asian Studies; Gale Group (Singapore Institute of Southeast Asian Studies, 2005)
Papers based on those given to the 2002 ISEAS conference in which historians explored many factors which relate to the writing of histories of nation-building.
Contemporary and national history: A double challenge -- Nation and state in histories of nation-building, with special reference to Thailand -- Rethinking history and "nation-building" in the Philippines -- Writing the history of independent Indonesia -- Ethnicity in the making of Malaysia -- Historians writing nations: Malaysian contests -- Writing Malaysia's contemporary history -- Forging Malaysia's contemporary history -- Forging Malaysia and Singapore: colonialism, decolonization and nation-building -- Nation-building and the Singapore story: some issues in the study of contemporary Singapore history -- Nation and heritage.
Electronic reproduction.
Keywords: Nation-building -- Southeast Asia; Electronic books; Southeast Asia -- Politics and government -- History; Southeast Asia -- History -- 20th century